Accounting conservatism and uncertainty in business environments; using financial data of listed companies in the Tehran stock exchange - Marziyeh Hejranijamil; Afsane Hejranijamil; Javad Shekarkhah (Emerald Publishing Limited, 2020)
Applying conservatism to the preparation of financial statements has been considered not only as a natural mechanism to protect the interests of the stockholders but also as a practical way to assist managers to deal with uncertainty in business environments. This study aimed to determine if increasing uncertainty can lead to raising the level of conservatism used in preparing financial statements. The result of the study could provide a better understanding of the factors that influence the level of applying conservative methods in accounting and financial reporting.The model introduced by Basu (1997) was used to measure accounting conservatism. Business strategy and alertness were considered as two proxies for classifying companies according to their level of uncertainty. By adding each proxy of uncertainty to the model and using the financial data of 183 companies for five years (from 2013 to 2018), the multiple regression models were estimated through EViews. It was assumed that inert companies and those with prospector strategy face a higher level of uncertainty. Consequently, they were expected to report their financial status conservatively.Findings revealed that companies, which adopted a prospector strategy, applied more conservative methods in their financial reports. This indicated that facing wider uncertainty results in reporting more conservatively, which could not be said about inert companies.The current research is the first research undertaken in a developing country such as Iran, and the study's results may benefit other developing countries.